PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM KERJA SEKOLAH TERHADAP KINERJA GURU - Carudin, Carudin (INVOTEC, 2011)
Improvement in teachers' teaching performance can be achieved by improving school leadership and school climate. This study aims: (a) to investigate the school leadership, school climate, and teacher’s performance, (b) to know how great the influence of school leadership and school climate on teacher’s performance. The study shows that the school principal leadership of State Vocational School (SMK) in Indramayu Regency, which includes dimensions of personality, decision-making ability, ability to communicate, motivate and delegate an authority, provides fair influence on performance. School climate also has fair influence on the performance of teachers. Teachers’ performance is in fair category. School leadership has a positive effect on the performance of teachers but is not enough (less fair) to motivate the performance. The school climate has less fair influence on teacher’s performance and can motivate the performance. School leadership and climate provide a significant positive impact on teacher’s performance.